Sports massage: A comprehensive review - Moraska, A. (The Journal of Sports Medicine and Physical Fitness, 2005)
The science of sports massage is of interest to many populations including athletes, athletic trainers, coaches, as well as sports physiologists. While evidence to support or refute the effects of massage on sports performance is insufficient to make definitive statements, new reports and trends within data help formulate an understanding of sports massage. This article will review sports massage research on topics including lactate clearance, delayed onset of muscle soreness (DOMS), muscle fatigue, the psychological effect of massage, and injury prevention and treatment. Articles referenced in Medline, Cochrane Database, the authors library, and references from articles are included in this review. Most studies contain methodological limitations including inadequate therapist training, insufficient duration of treatment, few subjects, or over or under working of muscles that limit a practical conclusion. Muscle soreness associated with DOMS is reduced with massage, although whether force recovers more quickly is still unclear. The research literature to date is insufficient to conclude whether massage facilitates recovery from a fatiguing effort. Both tissue healing and a psychological effect of massage are areas that may prove promising with further research. Results from published literature support a positive trend for massage to benefit athletic recovery and performance; a need for further research into sports massage, especially well-designed studies utilizing therapists specifically trained to administer this type of therapy, is warranted.